Bullying As a Joke: A Mixed Method Study Among Senior High School Students in Kupang City - Lette, Arman Rifat; Paulus, Aysanti Yuliana (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Bullying cases still often occur in the world of education, from elementary school to university level. Compared to other levels of education, bullying is more common among high school students. This type of research is mixed-method research. This type of quantitative research uses a descriptive-analytical method with a cross-sectional design while the qualitative approach is with an exploratory design and a phenomenological approach. The research was conducted in six selected senior high schools (SMA) in July-September 2020. The total sample was 310 respondents. Meanwhile, for qualitative research, the number of informants was 12 informants. Quantitative analysis was carried out in 2 stages, namely: descriptive analysis and inferential analysis to prove the correlation between variables, using the Chi-Square test. Meanwhile, qualitative data analysis was carried out using phenomenological analysis. The results showed that there was a correlation between knowledge and bullying behavior (0.029 less than 0.05), attitudes with bullying behavior (0.028 less than 0.05) and the social environment with bullying behavior (0.001 less than 0.05). In addition, students also assess or think that bullying is common among them, and it is considered a joke and can familiarize one another. Lack of understanding and awareness of bullying and its effects causes bullying behavior to occur frequently. It is necessary to establish clear rules and sanctions in schools to prevent bullying among students.  Abstrak: Kasus Bullying masih sering terjadi di dunia pendidikan, baik itu dari tingkat sekolah dasar sampai ke perguruan tinggi. Dibandingkan dengan tingkat pendidikan yang lain, kasus bullying lebih banyak terjadi di kalangan siswa SMA. Jenis penelitian ini adalah penelitian mixed method. Jenis penelitian kuantitatif dengan menggunakan metode deskriptif analitik dengan rancang bangun cross sectional study sedangkan pendekatan kualitatif dengan rancangan eksplorasi dan pendekatan fenomenologi. Penelitian dilakukan di 6 Sekolah Menengah Atas (SMA) yang terpilih pada bulan Juli-September 2020. Jumlah sampel sebanyak 310 responden. Sedangkan untuk penelitian kualitatif jumlah informan sebanyak 12 informan. Analisis kuantitatif dilakukan dengan 2 tahap, yaitu : analisis deskriptif dan analisis inferensial untuk membuktikan hubungan antar variabel, menggunakan uji Chi Square. Sedangkan analisis data kualitatif dilakukan dengan menggunakan analisis fenomenologi. Hasil penelitian menunjukkan bahwa ada hubungan antara pengetahuan dengan perilaku bullying (0.029 kurang dari 0,05), sikap dengan perilaku bullying (0,028 kurang dari 0,05) dan lingkungan sosial dengan perilaku bullying (0,001 kurang dari 0,05). Selain itu, Siswa juga menilai atau beranggapan bahwa bullying merupakan hal biasa di kalangan mereka, dan dianggap merupakan candaan serta dapat mengakrabkan satu dengan lain. Kurangnya pemahaman dan kesadaran akan bullying dan dampaknya menyebabkan perilaku bullying masih sering terjadi. Pembuatan aturan dan sangsi yang jelas di dalam sekolah perlu dilakukan untuk mencegah perilaku bullying di kalangan siswa.